Toxic effects of smokeless tobacco on female reproductive health: A review - C. Laldinsangi (Current Research in Toxicology, 2022)
The habitual consumption of tobacco in its various form is widespread and a serious public health issue globally. In particular, the use of smokeless tobacco has increased substantially due to its easy availability and misconception that it is relatively harmless compared to smoking. Tobacco use has been well established from numerous studies as a causative agent of devastating illnesses such as cancer, insulin resistance, hypertension, acute respiratory disease, osteoporosis, etc. Limited but growing evidence have also suggested its role in adversely affecting reproductive capabilities and outcomes in women of reproductive age and during pregnancy. This paper provides an updated review on available literature regarding the negative effects of smokeless tobacco use on female reproductive health, during pregnancy and its adverse consequences on the offspring. Existing data suggests the association between chronic smokeless tobacco use and impairment of ovarian morphology and function, oocyte quality, hormonal perturbations, fetal development and long-term health effects on the fetus. Improved understanding of these issues can contribute to better awareness of the dangers of smokeless tobacco products.